Understanding carpal tunnel syndrome. Issue 12 (December 2022) - Garcia, Jose Omar; Scott, Derek; Parikh, Parth; Curley, Kara L.; Turkmani, Ali
ABSTRACT: Carpal tunnel syndrome (CTS) is an entrapment neuropathy affecting the median nerve. Prevalence is estimated at 4% to 5% of the population. A solid understanding of the anatomy, presentation, and diagnostics is key to efficient diagnosis and appropriate referral. Both surgical and nonsurgical interventions have led to improved clinical outcomes. Clinicians who have an in-depth knowledge of CTS symptoms and treatment options can prepare patients and streamline referrals for improved patient outcomes.